Vasodilation of rat skeletal muscle arteries by the novel BK channel opener GoSlo is mediated by the simultaneous activation of BK and Kv7 channels - Zavaritskaya, Olga; Dudem, Srikanth; Ma, Dongyu; Rabab, Kaneez E.; Albrecht, Sarah; Tsvetkov, Dmitry; Kassmann, Mario; Thornbury, Keith; Mladenov, Mitko; Kammermeier, Claire; Sergeant, Gerard; Mullins, Nicholas; et al. (British journal of pharmacology, 2020)
Background and Purpose - BK channels play important roles in various physiological and pathophysiological processes and thus have been the target of several drug development programmes focused on creating new efficacious BK channel openers, such as the GoSlo‐SR compounds.